Voltage dip mitigation in distribution networks - Wei, Gongyu (2017)
The increasing growth of high-tech industries in modern society has brought about a huge challenge on the power supply system, especially on distribution systems. The high-tech industries like wafer fabrication, semiconductor manufacturers and petrochemical industries require a high power quality (PQ), and voltage dip is considered as one of the most important indicators in PQ issues. Voltage dip can cause failure of equipment and result in heavy economic damages. Mitigation of voltage dip is possible by injecting either a shunt current or a series voltage. Thus battery interfaced shunt or series inverter systems or so called voltage source converter (VSC) can be employed for voltage dip mitigation in distribution networks. In this research, voltage dips are simulated at the source side and load side in a distribution network. Different test cases for voltage dip conditions such as large magnitude and short duration, large magnitude and long duration, small magnitude and short duration, and small magnitude and long duration will be studied. In this project, both balanced and unbalanced voltage dips caused by short circuit faults will be simulated for different operating conditions in a distribution network using MATLAB/Simulink and effective voltage dip mitigation methods will be explored and implemented. Modeling of Uninterrupted Power Supply (UPS), Dynamic Voltage Restorer (DVR) and Static Synchronous Compensator (STATCOM) will be performed. Data analysis will be developed to show the possible solutions to different kinds of voltage dips in distribution systems. Also, power quality improved during voltage dips by mitigation devices will be demonstrated. This will help reduce the negative impact and avoid equipment failure on a very large scale. Key words: power quality, voltage dip mitigation, Matlab/Simulink, distribution network, UPS, DVR, STATCOM.